2022
DOI: 10.3389/fgene.2022.848364
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of Cardiac in a Rat Model Uncovers Potential Target LncRNA of Diabetic Cardiomyopathy

Abstract: Background: Diabetic cardiomyopathy (DCM) is one of the major causes of heart failure in diabetic patients; however, its pathogenesis remains unclear. Long non-coding RNAs (lncRNAs) are involved in the development of various cardiovascular diseases, but little is known in DCM.Objective: The present study was conducted to investigate the altered expression signature of lncRNAs and mRNAs by RNA-sequencing and uncovers the potential targets of DCM.Methods: A DCM rat model was established, and the genome-wide expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In this present study, we established the T1DM rat model by intraperitoneal injection of STZ and treatment with EMPA for 12 weeks to investigate changes in proteins and metabolites in the myocardium. The animal experiment results confirmed that diabetes contributed to a pronounced DCM characterized by mitochondrial dysfunction, impaired lipid metabolism, myocardial fibrosis, and associated diastolic and systolic functional impairments of the heart, which were consistent with the observations in previous studies ( 21 , 29 ). Dysregulation of metabolism increased production of AGEs and apoptosis, inflammation, and impaired calcium were all suggested to explain the cardiac impairment in DCM ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this present study, we established the T1DM rat model by intraperitoneal injection of STZ and treatment with EMPA for 12 weeks to investigate changes in proteins and metabolites in the myocardium. The animal experiment results confirmed that diabetes contributed to a pronounced DCM characterized by mitochondrial dysfunction, impaired lipid metabolism, myocardial fibrosis, and associated diastolic and systolic functional impairments of the heart, which were consistent with the observations in previous studies ( 21 , 29 ). Dysregulation of metabolism increased production of AGEs and apoptosis, inflammation, and impaired calcium were all suggested to explain the cardiac impairment in DCM ( 30 ).…”
Section: Discussionsupporting
confidence: 92%
“…The mitochondrial structure was further examined by standard transmission electron microscopy (TEM) in the laboratory of Guangzhou Huiyuanyuan Pharmaceutical Technology Co., LTD. Fresh myocardium sample preparation for TEM was performed as previously described ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…We then analysed the expression patterns of cardiac GABA A receptor subunits using RNA sequence data collected from rat 9 and human hearts. 10 Focusing on α, β and γ subunits, which consist of propofol and benzodiazepine binding sites (α-β subunit interface for propofol 12 and α-γ subunit interface for benzodiazepine 13,14 ), interestingly, none of the genes for γ subunits (GABRG1, GABRG2 and GABRG3) were detectable despite the presence of α and β subunits in both rat and human hearts (Figure 4A,B), while all these subunits are highly expressed in neuronal cells of the human brain (Figure S2).…”
Section: Gene Expression Analysis Of Gaba a Receptor Subunits In Rat ...mentioning
confidence: 99%
“…Additionally, in a clinical study, the effects of remimazolam on cardiac contractility and other haemodynamic parameters were compared with those of propofol during the induction of general anaesthesia. Finally, because propofol and remimazolam bind to different binding sites of GABA A receptors consisting of different subunits, the expression pattern of the subunits of GABA A receptor in the hearts was assessed using previous RNA sequence data in both rats 9 and humans. 10,11 2 | RESULTS 2.1 | Remimazolam does not possess a direct negative effect on cardiac contractility as opposed to propofol: A preclinical ex vivo study using isolated rat hearts…”
mentioning
confidence: 99%
“…Chronic hyperglycemia is associated with fibrosis-driven myocardial stiffness, cardiomyocyte hypertrophy, and altered substrate metabolism triggering structural and functional impairment in the cardiac tissue leading to DCM [ 2 5 ]. Glucose-induced progression of these cardiac pathologies is mediated through aberrant activation of the signaling pathways that are persuaded by changes in the cardiac transcriptome [ 6 , 7 ]. The underlying molecular mechanisms involved in this transcriptional reprogramming are poorly understood.…”
Section: Introductionmentioning
confidence: 99%